"Mala-Baklang Espasyo" sa Arkitekturang Filipino: Estetika, Morpolohiya, Konteksto (Panimulang Pagtuklas at Paggalugad) - Cabalfin, Edson Roy G. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 1)
-